THE PRICE COMPARISON STUDY OF ONLINE MOTORCYCLE TAXIS AND BASE MOTORCYCLE TAXI ACCORDING TO USERS - Rahman Saripudin; Tarita Aprilani Sitinjak (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2023)
Price is the amount of value that consumers exchange for the benefit of owning or using a product whose value is set by buyers and sellers through bargaining, or set by sellers for a price equal to all buyers. The price of online motorcycle taxis and base motorcycle taxis in the city of Palangka Raya is different, therefore the purpose of this study is to find out the comparison in terms of prices offered by providers according to users.The research method used was a quantitative descriptive method. The research was conducted by distributing questionnaires to users of online motorcycle taxis and base motorcycle taxis. the results of the study related to the price comparisons for online motorcycle taxis and base motorcycle taxis according to users based on data obtained from the results of 100 questionnaire respondents. The questionnaire consisted of 14 statements covering online motorcycle taxi and base motorcycle taxi price indicators, which are affordability, price competitiveness, price compatibility with benefits, price compatibility with quality, selling price, price discounts, ease of access, and security. From the calculation results, respondents prefer to use online motorcycle taxis, as seen from the mean value of online motorcycle taxis (27.86) ≥ base motorcycle taxis (18.06) and the value of the online motorcycle taxi mode obtained results of 5 (strongly agree) which means according to online motorcycle taxi respondents from the price indicator offered by the provider can be accepted by online motorcycle taxi respondents while the base ojek obtained 3 (doubtful) results which means according to base ojek respondents from the price indicator offered by the provider is less can be accepted by base ojek respondents.